Transperineal laser ablation of the prostate with EchoLaser™ system: perioperative and short-term functional and sexual outcomes - Sessa, Francesco; Polverino, Paolo; Bisegna, Claudio; Siena, Giampaolo; Lo Re, Mattia; Spatafora, Pietro; Pecoraro, Alessio; Rivetti, Anna; Conte, Francesco Lupo; Cocci, Andrea; Villari, Donata; Minervini, Andrea; et al. (Frontiers in Urology, 2022)
Objective To date, several ultra-minimally-invasive surgical techniques are available for the treatment of male LUTS due to benign prostatic obstruction (BPO). Herein we report our preliminary experience with SoracteLite™ TPLA for the treatment of carefully selected patients with LUTS due to BPO. Methods Data from all consecutive patients undergoing TPLA at our institution between April 2021 and February 2022 were prospectively collected in a specific database. Data regarding functional and sexual outcomes evaluated by validated questionnaires and uroflowmetry were analyzed. All the procedure were performed in an outpatient setting, under local anesthesia and conscious sedation, using EchoLaser device, a multisource diode laser generator. Results Overall, 38 patients underwent TPLA at our institution during the study period. The median prostate volume was 46 ml (IQR 38-71). The median time to complete the procedure was 31 min (IQR 28-37). All patients but one were discharged within 8 hours of hospital stay. No perioperative Clavien-Dindo grade ≥2 complications were recorded. Median improvement in Qmax was 17%, 24% and 32% at 1 month, 3 months and last follow-up after surgery; as a result, the median postoperative IPSS at 1 month, 3 months and at last follow-up decreased by -14%, -36% and -35%, respectively. All patients preserved ejaculatory and sexual function. Two patients (5%), catheter carriers before the procedure, experienced acute urinary retention after TPLA treatment and required replacement of an indwelling catheter. Conclusions TPLA can be a feasible, safe and effective ultra-minimally-invasive procedure for carefully selected patients with LUTS due to BPO.